The Force Phrase in Northern: Bahdinani Sub- Dialect - Abozaid, Sanya J.; Sulaiman, Mohammed Salih A. (Humanities Journal of University of Zakho, 2017)
This paper investigates " the Force Phrase in Northern: Bahdinani Sub- dialect". It aims at identifying those elements that realize Force of the utterance in Kurdish and their syntactic behavior throughout the levels of derivation of the utterance. The investigation is carried out within the framework of the Government and Binding Theory as developed in Chomsky (1981; 1986). We find this theory quite appropriate for analysis of Kurdish data as it provides multi-levels of analysis (DS; SS; LF; PF). The study Hypothesizes that in Kurdish two parameters of movement are available depending on the type of Force signaled by the utterance. Thus, in statements، the force element has no phonological realization when the clause is dependent ، but in dependent clauses the complementizer (ku) occupies the head position of the Force phrase. In questions، however، some interrogative words move overtly at S-structure to (Spec-Force P) ،while others move covertly to that position at(LF) ،and thus remain insitu at(PF).